IL-5 enhances the in vitro adhesion of human eosinophils, but not neutrophils, in a leucocyte integrin (CD11/18)-dependent manner. - Walsh, G M (1990)
In an attempt to explain the preferential accumulation of eosinophils at sites of allergic tissue reactions, we have studied the effects of interleukin-5 (IL-5) on the adherence of human eosinophils and neutrophils to plasma-coated glass (PCG) or human microvascular endothelial cells (HMVEC). IL-5 was compared with IL-3, granulocyte-macrophage colony-stimulating factor (GM-CSF) and platelet-activating factor (PAF), since all these agents have biological properties associated with eosinophil activation and/or survival in vitro. IL-5, IL-3 and GM-CSF induced a time-dependent increase in adherence of normal density eosinophils to PCG optimal at 60 min, whereas the effect of PAF was greater at 15 min. Similar results were obtained with neutrophils, with the exception that IL-5 had minimal and non-significant effects on this cell type. Unstimulated eosinophils and neutrophils also adhered to PCG or HMVEC, but in low numbers. Preincubation of eosinophils with IL-5, GM-CSF or PAF resulted in dose-dependent increases in the numbers of adherent cells to PCG. IL-3 had a smaller but significant effect on enhanced eosinophil adhesion to PCG, while IL-2 and lyso-PAF were ineffective. Neutrophils gave similar levels of baseline and stimulated adhesion to PCG as eosinophils, IL-5 again had no significant stimulatory effect. IL-5 also increased eosinophil, but not neutrophil, adherence to HMVEC in a concentration-dependent manner. Preincubation with the protein synthesis inhibitor cycloheximide had no effect on IL-5-, GM-CSF- or PAF-stimulated eosinophil adhesion. The contribution of the CD11/18 leucocyte integrins to IL-5- and PAF-induced eosinophil hyperadherence was investigated by inhibition experiments utilizing monoclonal antibodies (mAb). Enhanced adhesion to PCG (by PAF) or HMVEC (by IL-5) was inhibited by (ranked in order of potency) anti-CR3 alpha = common beta-chain greater than LFA-1 alpha. Anti-p150,95 alpha had no measurable effect. Baseline adhesion by unstimulated eosinophils was not significantly influenced by prior incubation with these mAb. Using flow cytometry, IL-5 and IL-3 were found to up-regulate cosinophil but not neutrophil CR3 expression. These findings demonstrate that IL-5 enhances cosinophil, but not neutrophil, adherence reactions, by a mechanism dependent, at least in part, on the CD11/18 family of adhesion glycoproteins.